Self-Reported Low Vitality, Poor Mental Health, and Low Dietary Restraint Are Associated with Overperception of Physical Exertion - Paula C. Chandler-Laney; David W. Brock; Barbara A. Gower; Jessica A. Alvarez; Nikki C. Bush; Gary R. Hunter (Journal of Obesity)
Objective. We investigated whether perceived exertion, in comparison to the physiological response to exercise, was associated with self-reported vitality, mental health, and physical function during daily activities, or weight control behaviors. Design. Weight-reduced, formerly overweight women (n=126, aged 22–46 years), completed health and dietary control questionnaires, and underwent a treadmill-walking task while heart rate, ventilation, respiratory exchange ratio, and ratings of perceived exertion were recorded. Results. Overperception of exertion (perceived exertion physiological exertion) was inversely associated with vitality (r=−0.190, P<.05), mental health (r=−0.188, P<.05), and dietary control (r values range −0.231 to −0.317, P<.05). In linear regression modeling, vitality or mental health, and cognitive dietary restraint were independently associated with accuracy of perceived exertion, independent of age, ethnicity, and engagement in exercise during weight loss. Each model explained 7%-8% of the variance in accuracy of perceived exertion. Conclusion. Women with low vitality or poor mental health, and poor dietary control may overperceive exertion. Such overperception may be a barrier to engage in physical activity and thus increase susceptibility to weight gain.